2009
DOI: 10.55095/achot2009/019
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Results of the CLS Acetabular Cup in Primary Total Hip Replacement

Abstract: PURPOSE OF THE STUDYTo evaluate the results of primary total hip replacement with the CLS acetabular cup at a minimum of 15 years of follow-up. MATERIAL AND METHODSA total of 105 patients, with 112 hips, undergoing hip arthroplasty with the use of CLS acetabular cup between 1991 and 1993 were evaluated. The group comprised of 33 men and 72 women with an average age of 51.3 years (range, 28 to 66) at the time of surgery. All patients received the CLS expansion cup with a polyethylene Sulen-type liner. Cemented … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Rozkydal and Pink [20], Parvizi et al [17] and Van Raaij et al [22] observed that soft tissue scaring, changes in the shape and slope of tibia plateau, as well as difficulties related to detaching the soft tissue of the proximal tibia are clinical conditions often related to TKA performed after high tibial osteotomy. According to the literature, technical difficulties in exposing proximal tibia and eversion of the patella mechanism using the conventional approach demand the use of an extended approach to obtain adequate surgical exposure of the knee joint [4,24].…”
Section: Discussionmentioning
confidence: 99%
“…Rozkydal and Pink [20], Parvizi et al [17] and Van Raaij et al [22] observed that soft tissue scaring, changes in the shape and slope of tibia plateau, as well as difficulties related to detaching the soft tissue of the proximal tibia are clinical conditions often related to TKA performed after high tibial osteotomy. According to the literature, technical difficulties in exposing proximal tibia and eversion of the patella mechanism using the conventional approach demand the use of an extended approach to obtain adequate surgical exposure of the knee joint [4,24].…”
Section: Discussionmentioning
confidence: 99%